Subhas: A political biography - Sitanshu Das; DAS (Sitanshu) (New Delhi Rupa & Co, 2001)
Subhas Chandra Bose is one of India's most controversial leaders. He was one of the few Indian leaders to attempt to win freedom by force and was a constant thorn in the side of the British, as well as Mahatma Gandhi. A revolutionary in every sense of the word, Bose spent his life haunted by a call of duty and would meet his death in attempting to answer that call in his own indomitable way. Subhas: A Political Biography explores the ideology and politics of a passionate intellect who sacrificed everything in his effort to win freedom for his country at any cost.
Keywords: Biography; Political Science